Incorporating the Jesness Inventory-Revised (JI-R) in a Best-Practice Model of Juvenile Delinquency Assessments. Issue 1 (1st January 2016) - Semel, Robert A.
ABSTRACT: This article examines use of the Jesness Inventory-Revised (JI-R) in the juvenile delinquency assessment context. The JI-R was identified by Hoge and Andrews (2010) among several standardized personality tests that are useful as part of a best-practice comprehensive juvenile forensic assessment. The JI-R is particularly relevant in forensic contexts with respect to identifying personality characteristics associated with juvenile delinquency. It is proposed that the JI-R can be integrated into the contemporary risk-need-responsivity (RNR) model of correctional assessment and rehabilitative programming and its application for juvenile delinquents. Studies suggest that the Jesness Inventory may identify an antisocial orientation dimension associated with dynamic risk-need factors in youths that influence criminal or delinquent behavior and that can be targeted for intervention. The JI-R also assesses internalizing psychological problems that may identify responsivity factors relevant for disposition and treatment planning in forensic contexts. This article identifies some technical limitations of the JI-R, including the issue of item overlap. The questionable effectiveness of this instrument in detecting response bias, especially underreporting, is also considered. Directions for future research are suggested.